Chapter I: journey to the West Kalimantan inspiration / Asmah Alia Mohamad Bohari and Ruth Lua Ejau - Mohamad Bohari, Asmah Alia; Ejau, Ruth Lua (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
The primary goal of this programme is to expose students to institutions in other countries through outward mobility. The prospects for establishing diplomatic links with students and institutions from other nations are expanded. At the same time, the students also receive a variety of experiences and learn about various customs and cultures. This programme is also in line with the UiTM GRU2025 mission. UiTM aims to become a Globally—renowned University by 2025. As a part of the overseas mobility delegation, the top students from each programme run by the Universiti Teknologi MARA Cawangan Sarawak's Centre of Studies of Art & Design, Architecture , Planning and Surveying were chosen. The involved programme s are the Bachelor of Science (Hons) in Architecture (AP243), Bachelor of Quantity Surveying (Hons) (AP224), Diploma in Building Technology (AP126), Diploma in Quantity Surveying (AP114), Diploma in Art & Design (Graphic Design & Digital Media) (CAD111), and Diploma in Fine Art (CAAD118). The mobility programme welcomed two post graduate students from the AP781 Master of Science (Built Environment) UiTM Cawangan Sarawak.